Mitigation of Consumptive Behavior through Financial Literacy and Saving Culture for Vocational High School Students - Indri Dithisari; Marlya Fatira AK; Ummanah; Ana Susanti Yusman; Chairunnisa Nur Fitriani; Ganda Permana (CSR International Journal, 2024)
PMKM Education on financial literacy and saving culture at the State Vocational High School (SMK) 7 Medan, Sitirejo II Village, Medan Amplas District, Medan City, North Sumatra, Aims to provide an understanding of Financial Literacy in daily life, the importance of saving culture for future financial planning, Overcoming excessive consumptive behavior. The school has never received education related to this material from any party. In order to run PMKM activities smoothly, the service team carried out data collection techniques by interviewing the State Vocational High School (SMK) 7 Medan, which was given by finding knowledge transfer through the Educational Seminar on Financial Literacy Education and Saving Culture. The cost of implementing PMKM activities is needed in the amount of Rp. 1,917,000.00 (One et al. Hundred and Seventeen Thousand Rupiah) and a certificate from Bank Sumut Syariah. This educational activity has shaped students' knowledge and skills about financial literacy, consumptive behavior, and saving culture until an average of 87.55% after service implementation is evidenced by a perfect understanding with a score of 100, increasing to 112 people (56%). However, the lack of educational programs that specifically discuss financial literacy, which also supports students in personal financial management and the prevention of financial problems, is a challenge that needs to be overcome. Through this activity, a joint commitment was formed between PT Bank Sumut Syariah and SMK Negeri 7 Medan to assist the student saving culture program, which is carried out regularly and form student knowledge and awareness to save and reactivate the habit of saving more broadly, creating awareness among SMK students about shared responsibility in maintaining discipline and financial responsibility